Superprotonic Conductivity of Guanidinium Organosulfonate Hydrogen-Bonded Organic Frameworks with Nanotube-Shaped Proton Transport Channels - Chen, Xu-Yong; Cao, Li-Hui; Bai, Xiang-Tian; Cao, Xiao-Jie; Yang, Dan; Gao, Yi-Da (Precision Chemistry, 2023)
Grasping proton transport pathways and mechanisms is vital for the application of fuel cell technology. Herein, we screened four guanidinium organosulfonate charge-assisted hydrogen-bonded organic frameworks (HOFs), namely, GBBS, G 3 TSPHB, G 4 TSP, and G 6 HSPB, which possess high hydrogen-bonded density proton transport networks shaped like nanotubes. These materials were prepared by self-assembly through charge-assisted interactions between guanidinium cations and organosulfonate anions, as well as by host–guest regulation. At 80 °C and 93% RH, the proton conductivity of GBBS, G 3 TSPHB, G 4 TSP, and G 6 HSPB can reach 4.56 × 10–2, 2.55 × 10–2, 4.01 × 10–2, and 1.2 × 10–1 S cm–1, respectively, with superprotonic conductivity. Doping G 6 HSPB into the Nafion matrix prepared composite membranes for testing the performance of fuel cells. At 80 °C and 98% RH, the proton conductivity of 9%-G 6 HSPB@Nafion reached a maximum value of 1.14 × 10–1 S cm–1, which is 2.8 times higher than recast Nafion. The results showed that charge-assisted HOFs with high proton channel density have better proton transport properties, providing a reference for the design of highly proton-conducting materials.